Analisis Pengukuran Daya Saing Destinasi Wisata Berbasis Tourism and Travel Competitiveness Index - Yuviani Kusumawardhani (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2019)
ABSTRACTPorter's theory of international competitiveness departs from his belief that classical economic theory that explains comparative advantage is inadequate. A country's competitiveness is determined by the ability of industries to innovate and improve their capabilities. Tourism is currently the star for countries to improve their performance. The Travel and Tourism Competitiveness Index can provide support for countries that want to improve their tourism competitiveness. Literature study in a journal entitled "Measuring Competitiveness Objectives: Application of the Competitiveness Index for Travel and Tourism (2007)" can be a benchmark for measuring Indonesia's tourism power. The advantages of Indonesian tourism so far are still based on the low price factor, but the low price factor is an effective competitiveness factor. This makes Indonesia need to improve other factors that can become more effective competitiveness factors, such as ICT Readiness, Air Transportation Infrastructure, Environmental Sustainability, Land and Port Infrastructure, and Tourist Services Infrastructure.Keywords: Competitiveness, Tourist Destinations, TTCI, Tourism ABSTRAKTeori Porter tentang daya saing nasional berangkat dari keyakinannya bahwa teori ekonomi klasik yang menjelaskan tentang keunggulan komparatif tidak mencukupi. Daya saing suatu negara ditentukan oleh kemampuan industri melakukan inovasi dan meningkatkan kemampuannya. Pariwisata saat ini menjadi primadona bagi negara-negara untuk meningkatkan perekonomiannya. Travel and Tourism Competitiveness Index dapat memberikan gagasan bagi negara-negara yang ingin meningkatkan daya saing pariwisatanya. Studi kepustakaan pada jurnal yang berjudul “Measuring Destination Competitiveness: An Application of the Travel and Tourism Competitiveness Index (2007)” dapat menjadi sebuah tolak ukur bagaimana mengukur daya saing pariwisata Indonesia. Keunggulan pariwisata Indonesia selama ini masih bertopang pada faktor harga yang murah, namun faktor harga murah pada kenyataannya bukan menjadi salah satu faktor daya saing yang efektif. Hal ini membuat Indonesia perlu melakukan peningkatan pada faktor lainnya yang dapat menjadi faktor daya saing yang lebih efektif, seperti pada ICT Readiness, Air Transportation Infrastructure, Environmental Sustainability, Ground and Port Infrastructure, dan Tourist Service Infrastructure.Kata Kunci: Daya Saing, Destinasi Wisata, TTCI, Pariwisata